1995
DOI: 10.1111/j.1467-8535.1995.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing educational software with audio: assigning structural and functional attributes from the SSF model

Abstract: Forty-five years of intuitive combinations of audio-visual information have produced only mixed results. This paper proposes a conceptual, case-based method for adding audio to software. This method, unlike the intuitive approach, requires the researcher to assign structural and functional attributes from the SSF Model to specific software activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…This fmding supported the results of Unit 1 in a previous study (Mann, 1995(Mann, , 1993, and the assumption that temporal sound affected attention to critical information. The results on the highlights data indicated that the positive fmding in that previous study may be related to achievement in Unit 1.…”
Section: Content Segmentssupporting
confidence: 93%
See 4 more Smart Citations
“…This fmding supported the results of Unit 1 in a previous study (Mann, 1995(Mann, , 1993, and the assumption that temporal sound affected attention to critical information. The results on the highlights data indicated that the positive fmding in that previous study may be related to achievement in Unit 1.…”
Section: Content Segmentssupporting
confidence: 93%
“…The integration of clues with personal experience to create responses defines a crucial tenet of generative learning, a central concept of Wittrock's (1992) functional model, and of constructivist learning from educational software (Jonassen, 1991;Reigeluth, 1991;Salomon, Globerson, & Guterman, 1989;Scardamalia, Bereiter, McLean, Swallow, & Woodruff, 1989;Tobias, 1991;Winn, 1991). This view is consistent with current constructivist theory about learning with computer-based speech (Higginbotham-Wheat, 1991;Loughner, 1987;Mann, 1992Mann, , 1993Mann, , 1995. The fourth factor that seemed to affect the conclusions was that elaboration was used by the learners to generate relations.…”
Section: Contributing Factorssupporting
confidence: 76%
See 3 more Smart Citations